Perancangan UI/UX Platform Pemesanan Katering Makanan Sehat Berbasis Web dengan Human-Centered Design - Aisha Novira; Osly Usman; Fauzan Fadlullah (Indo Publishing, 2026)
This study aims to design the UI/UX and develop a high-fidelity prototype of a web-based healthy food catering ordering platform named NutriGo using a Human-Centered Design approach. The research is grounded in systemic problems faced by consumers, including the absence of transparent menu and price information, reliance on manual communication, and order discrepancies due to the lack of a standardized order management system. This study applies the Waterfall method integrated with five stages of Design Thinking: Empathize, Define, Ideate, Prototype, and Test. The unit of analysis is prospective users of application-based healthy food catering services, using convenience sampling for 30 usability testing respondents and purposive sampling for 5 interview respondents. Data were collected through questionnaires, prototype testing scenarios, the System Usability Scale (SUS), and semi-structured interviews, then analyzed using SUS scoring based on Brooke (1996) and thematic analysis. The results show that the NutriGo prototype obtained an average SUS score of 81.33, which falls into the Excellent category and exceeds the minimum acceptance threshold, while all respondents expressed positive intentions on the three Behavioral Intention indicators: Intention to Use, Continuance Intention, and Recommendation Intention.